Musical Healing in Cultural Context - Gouk, Penelope (Aldershot Ashgate, 2000)
How do people use music to heal themselves and others? Are the healing powers of music universal or culturally specific? The essays in this volume address these two central questions as to music's potential as a therapeutic source. The contributors approach the study of music healing from social, cultural and historical backgrounds, and in so doing provide perspectives on the subject which complement the wealth of existing literature by practitioners.The forms of music therapy explored in the book exemplify the well-being that can be experienced as a result of participating in any type of musical or artistic performance. Case studies include examples from the Bolivian Andes, Africa and Western Europe, as well as an assessment of the role of Islamic traditions in Western practices.These case studies introduce some new, and possibly unfamiliar models of musical healing to music therapists, ethnomusicologists and anthropologists. The book contributes to our understanding of the transformative and healing roles that music plays in different societies, and so enables us better to understand the important part music contributes to our own cultures.
Introduction / Penelope Gouk -- Bodies of sound and landscapes of music: a view from the Bolivian Andes / Henry Stobart -- Theories of music in African ngoma healing / John M. Janzen -- Dancing the disease: music and trance in Tumbuka healing / Steven M. Friedson -- ’Spiritual medicine’: music and healing in Islam and its influence in Western medicine / Charles Burnett -- The inflected voice: attraction and curative properties / George Rousseau -- ’No pill’s gonna cure my ill’: gender, erotic melancholy, and traditions of musical healing in the modern West / Linda Phyllis Austern -- Soul music as exemplified in nineteenth-century German psychiatry / Cheryce Kramer -- The dancing nurse: kalela drums and the history of hygiene in Africa / Lyn Schumaker -- Sister disciplines?: Music and Medicine in historical perspective / Penelope Gouk -- Bibliography -- Index
Keywords: Cuckoo; Music therapy; Medicine